Work-related stress and result based performance of academic staff in Federal Polytechnics of South East Nigeria - Chioma Ijeoma , Eni, (International Journal of Scientific Research and Management (IJSRM), 2023)
The study investigated work related stress and result based performance of academic staff in Federal Polytechnics of South East Nigeria (Federal Polytechnic, Oko, Federal Polytechnic Nekede, Akanu Ibiam Federal Polytechnic Unwana Afikpo). Structured questionnaire was the principal tool used in eliciting information from three hundred and fifteen (315) respondents drawn from the study population. Descriptive statistics and regression analysis were used in data analysis. The result of the regression analysis shows that work related stress has a negative significant impact on the result based performance. The model summary and ANOVA results presented show that the model is highly fitted with no auto correlation with an overall significant regression. The researcher concludes that the commitment of educational stakeholders towards the welfare of academic staff will reduce work-related stress.